Glucocorticoid-induced microRNA-378 signaling mediates the progression of pancreatic cancer by enhancing autophagy - Liu, Li; Han, Shanshan; Xiao, Xi; An, Xuefeng; Gladkich, Jury; Hinz, Ulf; Hillmer, Stefan; Hoppe-Tichy, Torsten; Xu, Yi; Schäfer, Michael; Strobel, Oliver; Herr, Ingrid (Cell death & disease, 2022)
Glucocorticoids (GCs) are widely used in tumor therapy to reduce tumor growth, inflammation, edema, and other side effects. Controversially, GCs may also cause the progression of highly aggressive pancreatic ductal adenocarcinoma (PDAC). Because microRNA (miR) and autophagy signaling support the invasive growth of PDAC, we asked whether these mechanisms may be targeted by GCs. Six established human PDAC cell lines, tissue from patients who received GC medication (n = 35) prior to surgery, or not (n = 35), and tumor xenografts were examined by RT-qPCR, transmission electron microscopy (TEM), monodansylcadaverine (MDC) staining, immunohistochemistry, in situ hybridization, gene array and Kaplan-Meier analysis with bioinformatics, and MTT, western blot, colony, spheroid, migration, and invasion assays. We found that various GCs, including dexamethasone (DEX), induced typical features of macroautophagy with the appearance of autolysosomes, enhanced LC3-II, decreased SQSTM1/p62 expression and induced epithelial-mesenchymal transition (EMT) and gemcitabine resistance. The GC receptor (GR) antagonist mifepristone (RU486) counteracted DEX-induced autophagy features, suggesting that the GC-GR complex is involved in the induction of autophagy. The autophagy-related miR-378i and miR-378a-3p were selected as the top upregulated candidates, and their high expression in PDAC patient tissue correlated with low survival. siRNA-mediated downregulation of miR-378 inhibited DEX-induced autophagy, and tumor progression. Bioinformatics confirmed the contribution of miR-378 to the regulation of signaling networks involved in GC-induced autophagy and tumor progression. The construction of a molecular docking model revealed stable binding of miR-378 to the DEX-GR complex, suggesting direct regulation. These substantial, novel, in-depth data reveal that GCs favor autophagy-mediated cancer progression by inducing miR-378 and GR binding and implicate GR and miR-378 as new therapeutic targets.
Gesehen am 08.02.2023